Financial sector development, savings mobilization and poverty reduction in Ghana - Peter Quartey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The paper primarily investigates the interrelationship between financial sector development and poverty reduction in Ghana. This is done using time-series data from the World Development Indicators from 1970-2001. The main findings are, first, that even though financial sector development does not Granger-cause savings mobilization in Ghana, it induces poverty reduction; and second, that savings do Granger-cause poverty reduction in Ghana. Also, the effect of financial sector development on poverty reduction is positive but insignificant. This is due to the fact that financial intermediaries in Ghana have not adequately channelled savings to the pro-poor sectors of the economy because of government deficit financing, high default rate, lack of collateral and lack of proper business proposals. Another interesting finding is that there is a long-run cointegration relationship between financial sector development and poverty reduction.
Keywords: E2; E21; G2; 330; financial sector development; savings; poverty; Finanzsektor; Armut; Sparen; Ghana